Double-image encryption scheme based on the phase-truncated multiple-parameter Fresnel transform - Zhou, Ling; Zhou, Hang; Ma, Yan; Zhou, Nan-Run (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
A double-image encryption algorithm is proposed with the phase-truncated multiple-parameter Fresnel transform. Firstly, the pixel positions of two plaintext images are scrambled and then the results are merged into one image with the scrambling operation. Subsequently, the resulting image is encrypted by phase truncation and phase reservation in the multiple-parameter Fresnel transform domain. The phase information is scrambled by the affine transform and then recombined with the amplitude information. The final encryption image is obtained with the pixel scrambling and diffusion methods to further enhance the security of the image encryption system, where the scrambling and diffusion operations are based on logistic map, logistic-sine system and 2D logistic-adjusted-sine map. The image encryption scheme is robust against the common attacks due to the nonlinear properties of diffusion and phase truncation. Numerical simulation results verify the performance and the security of the proposed double-image algorithm based on the phase-truncated multiple-parameter Fresnel transform.
Optica Applicata, Vol. 52, 2022, nr 2, s. 163-177
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; chaotic system; phase-truncated multiple-parameter Fresnel transform; scrambling and diffusion operations; image encryption